Examining frustration intolerance beliefs among adults with dyslexia or developmental coordination disorder. (April 2022) - Potard, Catherine; Auger, Anne-Charlotte; Lenoir-Perrotel, Stéphanie; Jarry, Christophe
Highlights: Adults with DCD expressed higher frustration intolerance beliefs than typical peers. They also reported higher frustration intolerance beliefs than adults with dyslexia. Adults with dyslexia had higher discomfort intolerance than typical peers. Adults with dyslexia had higher achievement frustration than typical peers. Abstract: Background: Research suggests that adults diagnosed with specific learning disorders, such as dyslexia or developmental coordination disorder (DCD), are at greater risk of emotional problems related to frustration and anger. Aims: The purpose of this study was to investigate patterns of frustration intolerance beliefs among two groups of adults with a specific learning disorder (dyslexia or DCD), compared with typical adults. Methods and procedures: Participants were 235 French adults (students or in employment) with dyslexia ( M age = 35.8 years, SD = 13.3; females = 63 %), DCD ( M age = 32.9 years, SD = 11.8; females = 58 %) or typical development ( M age = 33.2 years, SD = 12.7; females = 65 %), who completed an online self-report questionnaire. Outcomes and results: Analysis of variance revealed a significant between-groups difference, as both learning disorder groups had higher frustration intolerance beliefs than the typical adults. Post hoc analysis showed that participants with DCD scored higher than those with dyslexia on each type of frustration intolerance belief, while participants with dyslexia scored higher than typical adults on achievement frustration and discomfort intolerance. Conclusions and implications: These results underline the usefulness of distinguishing between frustration intolerance dimensions, and of using rational emotive behavior therapy to reduce the irrational beliefs of people with DCD or dyslexia.